ANALYSIS OF THE PATTERNS OF DEVELOPMENT OF OLYMPIC AND PROFESSIONAL SPORTS (Physical Culture and Sport: Scientific Perspective, 2024)
The relevance of the topic is due to the importance of studying the trends and features of the functioning of the sports sector in the modern world. Sport is changing its key role in the social, cultural and economic development of society, promoting the popularization of a healthy lifestyle, uniting nations and establishing international dialogue. Insufficient theoretical and empirical research on the patterns of development of оlympic and professional sports limits the ability to predict their further progress, to formulate effective management decisions and strategies at the global and national levels. There is a need for a comprehensive analysis that takes into account the specifics of оlympic sport as a socio-cultural phenomenon and professional sport as an economic and entertainment sector. The purpose of the article is to study the main trends and factors influencing sports in the global context, and to analyze the ethical and legal aspects of the interaction between Olympic and professional sports. The stages of development of the modern Olympic movement demonstrate constant progress in its organizational, cultural and social aspects. Each stage reflects a response to the global challenges of its time, including political, economic and social transformations, which ensures the adaptation of Olympism to changes in the global community. Among the factors that negatively affect the development of professional sports today are the corruption aspects of professional sports activities,” which in the context of the analysis leads to the conclusion that the development and effectiveness of professional sports depends on the interaction of external and internal factors, including globalization, economic and social trends, technological transformations, demographic characteristics and competitive dynamics of sports organizations. At the same time, corruption is a key obstacle to progress, which negatively affects the development of professional sports. The development of Olympic and professional sports is largely determined by globalization, economic and social changes, technological innovations, demographic characteristics and competitive dynamics. At the same time, the fight against corruption and the improvement of anti-doping programs, especially in Ukraine, remain key challenges to ensuring progress in the sports sector.
Keywords: оlympic and professional sports; research; development factors